2003
DOI: 10.1007/s10295-002-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

An inexpensive medium for production of arachidonic acid by Mortierella alpina

Abstract: The production of arachidonic acid was studied in the fungus Mortierella alpina using an inexpensive medium. Glucose derived from maize starch hydrolysate was the sole carbon source and defatted soybean meal and sodium nitrate were the nitrogen sources. Optimal arachidonic acid yield (1.47 g l(-1)) was observed at a glucose concentration of 100 g l(-1). Various treatments of defatted soybean meal to extract soluble nitrogen nutrients were evaluated. Alkali extract was the most effective for arachidonic acid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Zhu et al [48] described a method for ARA production by M. alpina on glucose/defatted soybean meal and sodium nitrate with yields of 1.87 g/L ARA (17.3% of total lipids) from 31.2 g biomass in 7 days. Lan et al [49] showed that glutamate increased ARA production, while depressing other PUFAs.…”
Section: Production Systemsmentioning
confidence: 99%
“…Zhu et al [48] described a method for ARA production by M. alpina on glucose/defatted soybean meal and sodium nitrate with yields of 1.87 g/L ARA (17.3% of total lipids) from 31.2 g biomass in 7 days. Lan et al [49] showed that glutamate increased ARA production, while depressing other PUFAs.…”
Section: Production Systemsmentioning
confidence: 99%
“…Zhu et al (2003) described a method for ARA production by M. alpina on glucose/defatted soybean meal and sodium nitrate with the yield of 1.87 gl -1 ARA (17.3% of total lipids) from 31.2 g biomass in 7 days. Lan et al (2002) showed that glutamate enhanced ARA production, while other PUFAs were retained.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato hydrolyses waste was used by this fungi to produce fatty acids (15). Food waste, olive oil mill wastewater, industrial fats, whey, and starch hydrolysates are other wastes that have been used by oleaginous fungi to produce lipids (24)(25)(26)(27). The filamentous fungus Mortierella alliacea collects arachidonic acid, particularly in the form of triglycerides, in its mycelia and yields about 46.1 g.L -1 dry biomass.…”
Section: Discussionmentioning
confidence: 99%